Weak acidic stable carbazate modified cellulose membranes target for scavenging carbonylated proteins in hemodialysis. (1st March 2020) - Yang, Yifeng; Gao, Ming; Zhou, Bo; Cai, Peian; Larsson, Tobias E.; Zhao, Jinmin; Melander Bowden, Tim
Graphical abstract: Highlights: Carbazate modification is via a one-pot two-step reaction. Toxic protein clearance accomplished by carbazate- aldehyde/ ketone reaction. Modified CM was proved to remove toxic proteins in ESRD patients' serum. Modified CM is expected to improve clinical hemodialysis. Abstract: Carbazate groups were grafted on the commercial cellulose membrane (CM) to specifically scavenge the carbonylated proteins for hemodialysis. It confirmed that carbazate groups were successfully covalently attached on the CMs by XPS and EDS, and the modified CMs still saved their original morphology and crystalline structures by SEM and XRD. Furthermore, the modified CMs presented favorable physicochemical stability at wide pH range from 2.5 to 7.4. It was also found that the carbazate modified CMs could selectively remove carbonylated proteins from acrolein treated bovine serum albumin (BSA) or ESRD patient's blood serum in PBS buffer. The modified CMs showed the potential to be utilized as the substitute of dialysis membranes in hemodialysis.